The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1017/s000335610003508x
|View full text |Cite
|
Sign up to set email alerts
|

Protein levels in diets for European pigs in the tropics. 1. The effect of methionine supplementation on the protein requirement of growing pigs

Abstract: One hundred and twenty-eight Landrace and Large White pigs were allocated on the basis of sex, litter origin and initial weight to one of 16 treatments, made up of four basal 16, 18, 20 and 22% protein diets, each supplemented with either 0-00, 0-10, 0-15 or 0-20 % synthetic DL-methionine, at a common digestible energy level of 3740 kcal/kg. Pigs were reared between 8 and 50 kg live weight. Growth rate of pigs and efficiency of feed conversion were significantly improved as the protein levels were increased up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…Recently, however, Le Dividich and Canope (1978) reported much lower protein requirements for pigs reared in the tropics than obtained by the above workers. Fetuga et al (1975a and b) in agreement with Le Dividich and Canope (1978) suggested that the higher protein levels required were essentially due to a need to offset a deficiency of methionine and lysine in the food. The formulation of low cost but efficient diets for pigs reared under a tropical fPresent address: Department of Biochemistry, University of Ilorin, Ilorin, Nigeria.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Recently, however, Le Dividich and Canope (1978) reported much lower protein requirements for pigs reared in the tropics than obtained by the above workers. Fetuga et al (1975a and b) in agreement with Le Dividich and Canope (1978) suggested that the higher protein levels required were essentially due to a need to offset a deficiency of methionine and lysine in the food. The formulation of low cost but efficient diets for pigs reared under a tropical fPresent address: Department of Biochemistry, University of Ilorin, Ilorin, Nigeria.…”
Section: Introductionsupporting
confidence: 83%
“…It has been established that pig performance in terms of rate and efficiency of gain, and quality of the carcass, is closely related to the intake of particular nutrients, especially protein and energy (Cooke, Lodge and Lewis, 1972;O'Grady and Bowland, 1972;Fetuga et al, 1975a and b). This study clearly demonstrated that methionine deficiency in the diet of pigs will cause an 'amino acid imbalance' and depression of daily feed consumption, hence a decreased intake of essential nutrients with consequent adverse effects on daily live-weight gain, efficiency of food conversion and quality of the carcass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were slaughtered the following day, dressed and separated into two halves. The right sides were immediately dissected into lean bone and fat plus skin while the left halves were chilled for 24 h after which conventional carcass data were taken as described in detail by Fetuga, Babatunde & Oyenuga (1975a).…”
Section: Methodsmentioning
confidence: 99%
“…Dry seeds are roasted and eaten as a nutritionally balanced snack, while ground dry seeds are used to prepare many form of dishes such as Moi-moi, which is made from a steamed paste (Okpuzor et al, 2009). Bambara nut seed can be processed to make bread (Fetuga et al, 1975) and into vegetable milk similar to that made from soybean (Brough et al, 1993). The paste can be fried in oil and be served as snack with porridge at breakfast.…”
Section: Introductionmentioning
confidence: 99%